2013
DOI: 10.1007/s00221-013-3600-7
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal auditory sensory gating-out in first-episode and never-medicated paranoid schizophrenia patients: an fMRI study

Abstract: Numerous electrophysiological studies have showed auditory sensory gating-out abnormalities in chronic schizophrenia with antipsychotic medication. Previous research has used functional magnetic resonance imaging (fMRI) with excellent spatial resolution to identify the neural substrates of sensory gating-out deficits revealing increased hemodynamic response in the hippocampus, thalamus and prefrontal cortex. However, such results obtained from medicated patients may be confounded by antipsychotic medication. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Deactivations of the dorsolateral prefrontal cortex, hippocampus, insula, and thalamus were observed for P50 during SG ( 25 , 26 ). Unusual activations of hippocampus and thalamus were also observed in patients with schizophrenia ( 31 ). Based on these source findings, habituation to aversive noise likely reduced activity in these areas, inducing SG of P50, as observed in people with higher-scoring RR in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deactivations of the dorsolateral prefrontal cortex, hippocampus, insula, and thalamus were observed for P50 during SG ( 25 , 26 ). Unusual activations of hippocampus and thalamus were also observed in patients with schizophrenia ( 31 ). Based on these source findings, habituation to aversive noise likely reduced activity in these areas, inducing SG of P50, as observed in people with higher-scoring RR in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have reported that SG functions abnormally in patients with current and developing psychiatric illness ( 16 , 27 ). Patients with schizophrenia, for example, showed higher S2–S1 ratios, that is, lower SG, of the P50 component than non-schizophrenic controls ( 17 , 22 , 28 30 ), and attenuated activations in the bilateral thalamus and hippocampus ( 31 ). The SG deficit is likely related to malfunctions of early sensory and attentional processing, which may be related to modulation in the α7 nicotinic receptor system ( 32 ).…”
Section: Introductionmentioning
confidence: 99%